Axial compressive behavior of square CFST short columns with steel plate reinforcement - Ayce Cathen, Winti; Abdul Azim, Abdullah; Abdul Razak, Abdul Karim; Ahmad Kueh, Beng Hong; Bethany Guenevere, Bronny (Springer Nature Limited, 2026)
This study examines the axial compressive behavior of square concrete filled steel tube (CFST) short columns enhanced with steel plate reinforcement (SPR). Although CFST columns benefit from composite action, square sections exhibit reduced confinement effectiveness for the concrete core, increasing susceptibility to local buckling. While various strengthening methods are available, most of their implementation with prefabricated steel tubes is frequently impractical due to fabrication complexities that adversely affect construction efficiency. To overcome these issues, nine 100 mm × 100 mm × 300 mm square CFST short column specimens were tested experimentally under axial compression, including unreinforced, single SPR and double SPR configurations. SPR elements were spot welded internally to the steel tube walls to improve local stability with minimal fabrication complexity. Results confirm that SPR effectively delays local buckling onset, redistributes stress concentrations and enhances concrete confinement. Compared to unreinforced columns, specimens with SPR demonstrated increases in initial elastic stiffness (up to 63%), ductility (up to 39%) and ultimate axial compressive strength (up to 25%). Notably, double SPR configurations provided higher strength and energy absorption capacity, whereas single SPR delivered superior initial elastic stiffness and ductility, indicating a nonlinear performance relationship with reinforcement quantity. For analytical convenience, design equation is proposed to predict the axial compressive load capacity of square CFST short columns with SPR. These outcomes highlight SPR’s viability as a simple, efficient strengthening alternative, offering enhanced structural performance and constructability over established methods.